Modelling Future Sea-level Change under Green-house Warming Scenarios with an Earth System Model of Intermediate Complexity - Makarynskyy, Oleg; Kuhn, Michael; Featherstone, Will (Springer Verlag, 2004)
Recently, a lot of effort has been put into estimating possible near-future changes (say, 10-100 years) in the Earth's abiotic system, especially changes induced by human activities. One of the most studied issues is the effect of greenhouse gases on global warming and the corresponding change in sea-level around the world due to the associated de-glaciation. On a longer time-scale (>100 years), however, such climatic changes will affect the grav-ity field, location of the geocentre, and the Earth's rotation vector. In this study, the University of Victoria's (Canada) coupled Earth System Climate Model of intermediate complexity was implemented. The model was used to predict changes in global precipitation, ocean mass redistribution, and seawater salinity and temperature on timescales from hundreds to thousands years under two different greenhouse-warming scenarios. In future, the projected changes will be assimilated into an existing Synthetic Earth Gravity Model to determine the corresponding changes to the location of the geo-centre, the Earth's rotation vector, and the geoid.